Water soluble Chitosan Nanoparticle for the effective delivery of lipophilic drugs: A review - Singh K.; Mishra A. (My University, 2025)
Several polymeric nanoparticulate systems have been prepared and characterized in recent years, based on both natural and synthetic polymers, each with its own advantages and drawbacks. Among the natural polymers, chitosan has been studied extensively for preparation of nanoparticles. Chitosan nanoparticles have been reported with different characteristics with respect to drug delivery. Chitosan nanoparticle have gained more attention as drug delivery carriers because of their better stability, low toxicity, simple and mild preparation method, and providing versatile routes of administration. This review here presents the importance of chitosan nanoparticle as water soluble matter for the delivery of some lipophilic drugs mainly with the propofol delivery, the application of explored chitosan nanoparticles and its preparation methods.